Investor taxation, firm heterogeneity and capital structure choice - Magdalena Haring; Rainer Niemann; Silke Rünger (Arbeitskreis Quantitative Steuerlehre (arqus), 2016)
In this paper we analyze the effect of investor level taxes, firm-specific ownership structure and firm-specific payout policy on firms' capital structure choice. Our analysis is based on data for 10,983 firms from 13 Central and Eastern European (CEE) countries over the time period 2002-2012. Our results show a significant impact of the net tax benefit of debt on the debt ratio of firms. Ignoring firm heterogeneity, an increase in the net tax benefit of debt by 10 percentage points leads to an increase in the debt ratio of 2.49 percentage points. Taking into account investor-level taxation and firm heterogenity, an increase in the net tax benefit of debt of 10 percentage points leads to an increase in the debt ratio of only 1.27 percentage points, if the firm's largest individual domestic owner has more than 50% of the shares. If all individual domestic owners together have more than 50% of the shares, an increase in the net tax benefit of debt of 10 percentage points leads to a negligible increase in the debt ratio of 0.05 percentage points.
Keywords: G32; H24; H25; H32; 330; Eigentümerstruktur; Ausschüttungspolitik; Kapitalstruktur; Kapitalertragsteuer; Osteuropa